PENINGKATAN KEUNGGULAN BERSAING MELALUI KUALITAS PRODUK DAN PEMANFAATAN DIGITAL MARKETING PADA UMKM KULINER DI KOTA DENPASAR - I Made Wira Adi Kusuma; Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Putu Andini Desiyanti Laksmi (Nusantara Hasana Journal, 2022)
Increasing competitive advantage, product quality and the use of digital marketing is very important to pay attention to in improving the economy at Culinary MSMEs in Denpasar City. Especially in the absence of a decline in the level of the economy during this pandemic. This study aims to determine the influence of product quality on increasing competitive advantage through the use of digital marketing on Culinary MSMEs in the city of Denpasar. This research was conducted quantitatively and used questionnaires as a data collection method. The population used in this study was the owners of Culinary MSMEs in Denpasar, with the number of samples in this study being 50 culinary MSME owners in Denpasar. The sample used in this study was a saturated sample.  This research was conducted quantitatively and used questionnaires as a data collection method. Using IBM SPSS 25 analysis, the results were obtained that the first product quality has a positive and significant effect on the use of digital marketing in Culinary MSMEs in Denpasar. The second is the use of digital marketing has a positive and significant effect on increasing competitive advantages in Culinary MSMEs in Denpasar. Product quality directly affects the increase in competitive advantage in Culinary MSMEs in Denpasar. And the results of the analysis using Path Analysis (Path Analysis) to test the influence of variable intervening, it can be known the use of digital marketing which is an important variable as a mediator on competitive advantages and product quality.